Migrant motherhood: Maternal and child health care utilization of forced migrants in Mumbai, Maharashtra, India. (March 2020) - Pardhi, Ashish; Jungari, Suresh; Kale, Parshuram; Bomble, Priyanka
Highlights: This study used qualitative approach to document the forced migrants pregnant women problems. The study found that pregnant women not having adequate sanitation, nutrition and rest. Pregnant women have missed important ANC care services. Children in the destination missed important immunisation. Abstract: Background: It is widely acknowledged that climate change will lead to more frequent natural disasters and extreme weather events. This is a matter of concern, especially for countries like India which is amongst the most vulnerable drought-prone countries in the world. In 2015 the Government of Maharashtra had declared a drought in state. The severe drought situation forced millions of people to migrate from the Marathwada region to the bigger cities. Objective: The objective of the study was to examine the sanitation, hygiene and living conditions of migrants who were forced to leave their homes because of the drought. The focus of the study was on the health problems of pregnant migrant women and children in their destinations. Methods: The study adopted a qualitative approach to explore this phenomena. Fifteen in-depth interviews were conducted which included ten pregnant women and five women who had children less than two years of age. Data analysis were carried out with thematic analysis using NVivo software. Results: The study shows that pregnant mothers and women with children are at greater risk of diseases at place of destination. In particular, the pregnant migrant mothers could not access the necessary antenatal care. Moreover, they could not sleep or rest during the day due to non-availability of place.